2016
DOI: 10.1016/j.jsat.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Long-Term Health Related Quality of Life Trajectories of Individuals With Opioid Use Disorder

Abstract: Objectives Health related quality of life (HRQoL) has been increasingly considered an endpoint in evaluations of treatment for substance use disorders. We aimed to characterize longitudinal patterns of HRQoL in individuals with opioid use disorder (OUD) and with a history of opioid agonist treatment (OAT) with methadone. Methods The EuroQol EQ-5D, a preference-weighted measure of HRQoL, was assessed in individuals with OUD and with a history of OAT enrolled in three prospective cohort studies between Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…In contrast, we found psychiatric problems at baseline and recent receipt of pharmacotherapy for OUD treatment to be associated with HRQoL trajectories in at least one class. Discontinuation of pharmacotherapy for OUD was not associated with HRQoL in Nosyk (2011); Krebs et al (2016) found that pharmacotherapy for OUD was not a factor in developmental trajectories of HRQoL, while Nosyk et al (2015) found that pharmacotherapy had a positive impact on HRQoL across all sub-groups. Our results do not help to clarify these associations as we found pharmacotherapy to have a heterogenous association on HRQoL over time.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In contrast, we found psychiatric problems at baseline and recent receipt of pharmacotherapy for OUD treatment to be associated with HRQoL trajectories in at least one class. Discontinuation of pharmacotherapy for OUD was not associated with HRQoL in Nosyk (2011); Krebs et al (2016) found that pharmacotherapy for OUD was not a factor in developmental trajectories of HRQoL, while Nosyk et al (2015) found that pharmacotherapy had a positive impact on HRQoL across all sub-groups. Our results do not help to clarify these associations as we found pharmacotherapy to have a heterogenous association on HRQoL over time.…”
Section: Discussionmentioning
confidence: 96%
“…There are several sources of possible variation between our results and the previous studies noted above. First, in contrast to Nosyk et al (2011;2015) and Krebs et al (2016), we statistically defined latent class and estimated model parameters simultaneously in the GSE-RM framework. Nosyk et al (2015) relied on sub-group selection based on treatment modalities and not based on statistical methods of class assignment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, decreases in substance use during and after treatment have been associated with improvements in HRQoL. For example, clients in treatment for opioid use disorders have shown HRQoL improvement, although this may level off over time in treatment (Karow et al 2011, Krebs et al 2016, Nosyk et al 2015). Abstinence at 6 months post-inpatient detoxification has been associated with improved quality of life in the physical, mental and relationship domains, and successful recovery has been shown to be predictive of improved HRQoL in the subsequent year (Vederhus, Birkeland, and Clausen 2016, Garner et al 2014).…”
Section: Introductionmentioning
confidence: 99%